HUBUNGAN BERAT BADAN LEBIHÂ DAN KECEMASAN DENGAN HASIL TES ROLL DEPAN SENAM LANTAI PADA SISWA KELAS VIII SMP NEGERI 3 SIDOARJO - JURAWAL RIFIANTO, ARGO (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Over weight is body weight that to big or to fat, it is cause of over consume of calorie and without any energy using. Over weight can influence to body moving which is can makes forward roll test fail. Beside over weight, student’s worry’s different may can influence about forward roll test. The goal of this research is to know the relation of worry and floor gymnastic forward roll test value of 8th grader of SMP Negeri 3 Sidoarjo, and to know how many big influence of over weight and worry with floor gymnastic forward roll test value of 8th grader of SMP Negeri 3 Sidoarjo. This research is non-experiment research with quantitative and correlation design. Population on this research is all of 8th grader SMP Negeri 3 Sidoarjo which is 289 students. Than sampling technic which is use is purposive sampling with 60 students as a sample. The instrument on this research is IMT/U for body weight, worry questioner, and floor gymnastic forward roll test. Data analysis which is use is logistic regression. Base on the data analysis knows that between over weight with forward roll test has sig value 0,097> p value (sig) 0,05, so Ho accept and Ha ignore. So, there is no relation between over weight with forward roll test value. Than between worry with forward roll test has sig value 0,001>p value (sig) 0,05. So, Ho2 ignore and Ha2 accept. So, there is a relation between worry and forward roll test value. For counting of the relation over weight and worry with forward roll test value can see on logistic regression counting which is has sig value 0,001> p value (sig) 0,05. So, there is a relation between over weight and worry with forward roll test value The conclusion is, there is a significant relation between over weight and worry with floor gymnastic forward roll test value of 8th grader SMP Negeri 3 Sidoarjo as big as 41,7%. Keywords: over weight, worry, forward roll test.